Quantum Mechanical Studies of Three Aromatic Halogen-Substituted Bioactive Sulfonamidobenzoxazole Compounds with Potential Light Harvesting Properties. (19th August 2021) - Sheena Mary, Y.; Ertan-Bolelli, Tugba; Thomas, Renjith; Krishnan, Akhil R.; Bolelli, Kayhan; Kasap, Esin Nagihan; Onkol, Tijen; Yildiz, Ilkay
Abstract: Three different organic compounds, 2-phenyl-5-(4-trifloromethyl phenyl sulfonamido) benzoxazole (PTPS), 2-(4-chlorobenzyl)-5-(2, 4-dinitrophenylsulfonamido)benzoxazole (CNSB) and 2-(4-fluorobenzyl)-5-(2, 4-dinitrophenylsulfonamido)benzoxazole (FBPS), were synthesized. To find their energetically stable conformation, geometry optimization was done using density functional theory with the level B3LYP/cc-pVDZ. Electron distribution of the system was studied using molecular electrostatic potential map. Different intermolecular interactions arising from hyperconjugative effect were investigated using the natural bond orbital (NBO) formalism. Nonlinear optical properties were further studied using first-order hyperpolarizability values. The three compounds may be important in the development of novel inhibitor molecules of Topoisomerase II enzyme, as lead compounds. Light harvesting efficiency of PTPS is 0.9342, which shows that it is having potential applications in the design of new DSSC's.